TYPOLOGY OF EAST JAVA KIYAI IN RESPONSE TO MISYA - Nasiri; Ulum, Miftahul (International Journal of Psychosocial Rehabilitation, 2020)
East Java is the largest province of the number of Islamic Boarding School (Pesantren). So pesantren graduates become religious leaders who have a variety of thoughts. These figures are usually called kiyai (scholar). There are four typologies of East Javanese chaplain in understanding the practice of mating misya>r. First, the kiyai whose way of thinking is based on the instinct or intuition of the inner eye. This type of thinking model includes the typology of gnostic thinking. In responding to misya>r marriage, they argued that marriage misya>r should not be carried out absolutely, because this marriage had deviated from the original purpose of to be shari>’ah it and also in practice found deviations. Second, the kiyai whose way of thinking always puts forward the facts seen. This type of thinking model is a typology of positivistic thinking. In response to misya>r marriage, they argue that marriage is only allowed in the Middle East and cannot be done in Indonesia. That is because the condition of the Middle East community is different from the Indonesian people. Third, the kiyai whose way of thinking only pays attention to the sacred texts without regard to the condition of the community. This kind of thinking model includes the rhetorical thinking typology. In response to misya>r marriage, they argue that the practice of marrying misya>r may be carried out absolutely, because the elements of Islamic marriage have been fulfilled. Fourth, the kiyai whose way of thinking always combines text with context. This kind of thinking model includes the typology of demonstrative thinking. In connection with the marriage of misya>r, they argue that this marriage model cannot be done in all places, but for Middle Eastern people and their homes in the Middle East, it is permissible to choose the marriage model for misya>r, provided that they must follow the prevailing laws and regulations in his country.